Data-driven strength and conditioning, and technical training programs for goalkeeper`s diving save in football - Ibrahim, R.; de Boode, V.; Kingsma, I.; van Dieën, J. H. (Sports Biomechanics, 2025)
The goal of this study was to evaluate the technical and physical adaptations to a data-driven 12-weeks training programs that incorporated recent findings from biomechanical studies on the diving save. Three-dimensional kinematics and kinetics were collected and analysed from 11 goalkeepers diving to save high (190 cm) and low (30 cm) balls at three occasions: twice pre-training and once post-training. Intraclass correlation coefficients were found to be excellent (>.7) between the pre-training tests, and there were no learning effects between them. Three-way repeated measures ANOVAs were used to evaluate the effect of dive side, dive height and training programme (pre- vs post-training) on normalised dive time [s·m-1], average centre of mass (CoM) horizontal velocity [m·s-1] and total power [W] generated at contralateral and ipsilateral push-offs. Compared to pre-training, the post-training results revealed greater average CoM horizontal velocity (+.82 m·s-1, 95% CI = [.62, 1.02]) and power (+523 W, 95% CI = [313, 732]) at contralateral push-off. These adaptations caused a reduction in normalised dive time (- .008 s·m-1, 95% CI = [- .014, - .002]) at post-training compared to pre-training. This translates to 42 cm more goal area coverage in a penalty situation.